2020
DOI: 10.3389/fphar.2020.00689
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Pulsed Ultrasound Alleviates Hypoxia-Induced Chondrocyte Damage in Temporomandibular Disorders by Modulating the Hypoxia-Inducible Factor Pathway

Abstract: Temporomandibular disorders are a common cause of chronic pain in the orofacial region and have a complex and multi-factorial pathophysiology. Mechanical loading or inflammatory conditions have been shown to decrease oxygen tension within the joint cartilage and activate the hypoxia-inducible factor (HIF) pathway, which in turn aggravates the pathological processes underlying temporomandibular joint (TMJ) disorders. We previously showed that low-intensity pulsed ultrasound (LIPUS) treatment effectively repairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Primary temporomandibular condylar chondrocytes were isolated from 3-week-old healthy male Wistar rats (SPF Biotechnology, Beijing, China). The steps for the isolation and culture of these cells were based on a procedure previously published by our group ( Yang et al, 2020 ). Third-generation chondrocytes were incubated in six-well plates (Corning, United States) in the following three groups: normal group (N group), cultured in an atmosphere containing 5% oxygen; low oxygen tension group (L group), cultured in an atmosphere containing less than 1% oxygen; and low oxygen tension + LIPUS treatment group (LP group), incubated in an atmosphere containing less than 1% oxygen and subjected to LIPUS stimulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary temporomandibular condylar chondrocytes were isolated from 3-week-old healthy male Wistar rats (SPF Biotechnology, Beijing, China). The steps for the isolation and culture of these cells were based on a procedure previously published by our group ( Yang et al, 2020 ). Third-generation chondrocytes were incubated in six-well plates (Corning, United States) in the following three groups: normal group (N group), cultured in an atmosphere containing 5% oxygen; low oxygen tension group (L group), cultured in an atmosphere containing less than 1% oxygen; and low oxygen tension + LIPUS treatment group (LP group), incubated in an atmosphere containing less than 1% oxygen and subjected to LIPUS stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…With an intensity of 45 mW/cm 2 , the optimal effect is achieved after at least 2 weeks of treatment ( Liang et al, 2020 ). Moreover, in vitro simulation of a hypoxic environment has revealed that LIPUS can slow cartilage damage by upregulating HIF-1α and downregulating the HIF-2α pathway ( Yang et al, 2020 ). Current studies of cartilage, synovial fluid, serum and urine associated with joint disease utilizing proteomics aim to understand the pathogenesis and progression of arthritis ( Hsueh et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, He et al proved that LIPUS protected TMJDs through upregulating ZNT-9 (Zn2+ exporters), which further downregulated the crucial ECM-degrading effector enzymes MMP-3, ADAMTS-5, and ADAMTS-8 (He et al, 2021). According to Yang et al, LIPUS therapy restored the functions of damaged mandibular chondrocytes both in vitro and in vivo through modulating the hypoxia-inducible factor (HIF) pathway (Yang et al, 2020).…”
Section: Yang Et Al (2020)mentioning
confidence: 99%
“…A systemic review and meta-analysis even defined LIPUS as the most effective method for treating bone nonunion besides surgery [19]. In addition, several studies explored the therapeutic effects of LIPUS on cartilage tissue injury of the temporomandibular joint (TMJ) in the last 5 years and found that LIPUS could effectively suppress temporomandibular joint disorders (TMDs) in rats, which was caused by chronic sleep deprivation (CSD) intervention [20][21][22]. A recent review article also confirmed the effect of LIPUS on osteoarthritis of the TMJ [23].…”
Section: Introductionmentioning
confidence: 99%